Voting in corporations - Alan D. Miller (Theoretical Economics, 2021)
I introduce a model of shareholder voting. I describe and provide characterizations of three families of shareholder voting rules: ratio rules, difference rules, and share majority rules. The characterizations rely on two key axioms: merger consistency, which requires consistency in voting outcomes following stock-for-stock mergers, and reallocation invariance, which requires the shareholder voting rule to be immune to certain manipulative techniques used by shareholders to hide their ownership. The paper also extends May's theorem.
Keywords: D71; G34; K22; 330; Shareholder voting; axioms; share majority rule; merger consistency; reallocation invariance; one share-one vote; difference rules; ratio rules